Biomechanics-inspired game analysis of the rural e-commerce ecosystem: An analogy of intercellular interactions among four main entities - Sun, Lihong; Shu, Hui (Molecular & Cellular Biomechanics, 2025)
Biomechanics is becoming increasingly important in the field of biomedical science, impacting areas such as molecular biology and nanotechnology. This study draws on the principles of biomechanics to analyze the rural e-commerce ecosystem, focusing on the analogy of intercellular interactions among new farmers, e-commerce platforms, logistics companies, and local governments. The purpose of this study is to construct a four-party evolutionary game model that encompasses the dynamic interactions and strategic behaviors within the rural e-commerce ecosystem, aiming to explore the cooperative dynamics and strategic evolution among these four main entities. From a biomechanical perspective, treating these entities as “cells” and market forces as “mechanical signals,” we apply game theory and numerical simulation to analyze their strategic choices and the stability of the ecosystem at different evolutionary stages. The study finds that: government subsidies have a double-edged sword effect, stimulating the adoption of e-commerce, but requiring careful adjustment to prevent market imbalances. Cooperation between e-commerce platforms and logistics companies is crucial for improving supply chain efficiency. The strategic shift of new farmers towards active use of e-commerce is vital for the upward movement of agricultural products. System stability is a dynamic balance influenced by subsidy policies, the degree of cooperation, and the willingness of new farmers to adopt e-commerce. This research provides a new perspective for understanding strategic interactions by introducing biomechanical concepts into the analysis of business ecosystems. In practice, it offers actionable insights for policymakers and industry players to optimize the rural e-commerce ecosystem, promoting agricultural modernization and rural revitalization.